Violencia familiar y resiliencia en adolescentes de una institución educativa privada de Ayacucho, 2021 - Vega Burgos, Sara Janet (2022)
The main objective of this research was to determine the relationship between family violence and resilience in adolescents from a private educational institution in Ayacucho, 2021. Regarding the type of research, it is descriptive - correlational, with a non-experimental cross-sectional design. The population consisted of 350 students and a sample of 150 collaborators was obtained through non-probabilistic sampling at the author's convenience, in terms of instruments, to measure the family violence variable, the VIFA questionnaire and the ER - 14 questionnaire were used to the resilience. Regarding the most important findings, it is evident that there is an inverse connection Rho Spearman = -.485; given that the inverse relationship between family violence and the personal competence dimension Rho Spearman = .-515 and the acceptance of oneself and life dimension Rho Spearman = .-449 is observed. On the other hand, the inverse relationship between resilience and the physical violence dimension Rho Spearman = .-400 and the psychological violence dimension Rho Spearman = -.523 is observed. Similarly, the levels according to gender are observed, showing an average level of family violence of 72.3% in men and 59.7% in women; while, in the resilience variable, in the ladies, a medium level is observed with 52.2%, while in the men 25.3%. Finally, the existence of significant differences in both variables with respect to gender was demonstrated. In conclusion, the variables are inversely related.